Comparison of various pulpotomy techniques: coronal, cervical, and full pulpotomy - Alamri, Abdulrahman Saeed; Alqurashi, Asem Mustafa; Alotaibi, Fatimah Ayedh; Alghamdi, Ziyad Saleh; Salamah, Samar Khalid; Alenezi, Majed Awad; Almutairi, Waad Majed; Almutairi, Amjad Majed; Alabbasi, Daliya Mohammed (International Journal Of Community Medicine And Public Health, 2023)
The preservation of deciduous teeth is crucial in pediatric dentistry to maintain normal speech, development, and self-esteem, while also preventing secondary issues like space loss and tooth impaction. Different materials and approaches have been explored over time, ranging from mummification to maintaining pulp vitality and promoting healing. In today’s conservative dentistry, techniques like indirect pulp treatment and partial pulpotomy (PP) have gained popularity. Adults diagnosed with irreversible pulpitis due to deep caries often receive root canal therapy (RCT). However, coronal pulpotomy treatment (CPT) has emerged as an affordable alternative for those unable to afford RCT. CPT removes the coronal pulp, allowing the remaining pulp to remain vital. PP and complete pulpotomy are explored as treatments for teeth with signs of irreversible pulpitis. Success depends on eliminating infected tissue, using aseptic techniques, and achieving a tight restorative seal. Materials like MTA have shown favorable outcomes. Direct pulp therapy and PP can effectively preserve vital pulp in primary and young permanent teeth. The choice of pulpotomy material, such as MTA, plays a significant role in success rates.